FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT NASABAH BANK DALAM PENGGUNAAN FASILITAS E-BANKING YANG TERTERA PADA PERATURAN BANK INDONESIA NOMOR: 11/11/PBI/2009 - Fetri Setyo Liyundira; Deni Juliasari (UNEJ e-Proceeding)
This information system began to be required and used in various sectors. As in the banking sector, when the bloom once the use of Internet Banking as a tool or medium to conduct banking transactions. The information system has become one of the primary needs that is used in part of the banking system at this time. A study related to the management information systems to comply with the Regulation of Bank Indonesia (RBI). Sources of data in this study using internal data obtained using a questionnaire. Results showed that RBI concerning the use of Internet banking services are still not fully understood and the demand by the people who have over 35 years of age because of the possibility they only know to deposit, transfer and withdraw cash through the Bank only. Knowledge of information systems in the use of E-Banking service can not be separated from his individual interest in terms of benefits, ease of use and customer confidence. The knowledge possessed by the customer and interest arising from the individual can enhance a good reputation for the Bank.